Recent changes in London English. An overview of the main lexical, grammar and discourse features of Multicultural London English (MLE) - Palacios Martínez, Ignacio Miguel (Complutense Journal of English Studies, 2021)
This paper is intended to provide an overview of the main lexical, grammar and discourse features of the so-called Multicultural London English (MLE), a recent multiethnolect that can be regarded as a new development of London popular speech with the addition of traits from a pool of other sociolects and varieties of English, namely Caribbean and Jamaican English, and with a high proportion of young speakers. The data here analysed have been extracted from multiple sources, such as the London English Corpus (LOE), the Bergen Corpus of London Teenage Language (COLT), dictionaries, magazines, films, TV series, song lyrics and social media, mainly Twitter. Particular attention is paid to those grammar and discourse features which can be considered as the most innovative, such as the quotative this is + pronoun, man used as a personal pronoun, the overuse of a set of vocatives (brother, mate, boy, guy(s), bastard, dickhead), the invariant tags innit and you get me, the adjectives proper and bare used as intensifiers, a high presence of negative vernacular forms (ain’t, third person singular don’t), never as negative preterite and a high proportion of negative concord structures. As regards lexis, a wide range of borrowings and loan words from other varieties and languages are recorded together with an excessive amount of general vague nouns and general extenders.